Avaliação antifúngica do óleo essencial de Cinnamomum zeylanicum Blume como promotor do controle do gênero Penicillium do ar ambiental em sistema industrial alimentar - Sousa, Patrícia Pinheiro Rafael de (2011)
The majority fungal species identified in the food industry environment were Aspergillus flavus, Aspergillus niger and Penicillium spp., the latter being identified with higher relative frequency (71.70%) the Penicillium gender. The microbiological screening on 14 essential oils against 14 Penicillium spp. strains was performed in order to facilitate safe alternatives for control and/or elimination of this fungus. The average results for inhibition halos were 13.30 to 42.20 mm, whose oils from Cinnamomum zeylanicum, Cymbopongon citratus, Syzygium aromaticum, Origanum vulgare showed greater activity and those from Rosmarinus officinalis, Eucalyptus globulus, Laurus nobilis and Sassafras albidum showed no significant activity against tested strains. The essential oil of Cinnamomum zeylanicum Blume (OE) showed greater effectiveness and was used to determine the minimum inhibitory concentration (MIC) to assess its effect on mycelial growth and spore germination by using EO and chlorine solution Vega® (VG), commonly used in industry. MIC values obtained range from 256 to 512μg/mL both for EO and VG. The observed effect on the radial growth was concentration dependent for both products. On the spores germination, EO showed higher effectiveness compared to VG interfering with conidia germination. The EO emerges as an excellent alternative to be used for Penicillium control, since VG needed higher concentration though not having the same EO effectiveness.